2017
DOI: 10.3390/ma10040410
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Thermal Expansion and Thermal Contraction

Abstract: Thermal expansion is an important property of substances. Its theoretical prediction has been challenging, particularly in cases the volume decreases with temperature, i.e., thermal contraction or negative thermal expansion at high temperatures. In this paper, a new theory recently developed by the authors has been reviewed and further examined in the framework of fundamental thermodynamics and statistical mechanics. Its applications to cerium with colossal thermal expansion and Fe3Pt with thermal contraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 37 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…However, the statistical probability of the stable ferromagnetic configuration starts to decrease around 230 K and become lower than 50% at temperatures higher than 460 K with the rest being the combination of over 500 nonstable spin-flipping configurations, resulting in a negative thermal expansion between 289 and 449 K . Similar observations were made for Ce with only three configurations considered and other materials. ,,, …”
Section: Mg Complexessupporting
confidence: 66%
See 1 more Smart Citation
“…However, the statistical probability of the stable ferromagnetic configuration starts to decrease around 230 K and become lower than 50% at temperatures higher than 460 K with the rest being the combination of over 500 nonstable spin-flipping configurations, resulting in a negative thermal expansion between 289 and 449 K . Similar observations were made for Ce with only three configurations considered and other materials. ,,, …”
Section: Mg Complexessupporting
confidence: 66%
“…In our recent publications, we demonstrated that the probabilities of nonstable configurations play a central role in the prediction of critical phenomena and associated property anomalies. 18,19 It was shown that, on the basis of the free energy comparison of Fe 3 Pt with various magnetic configurations under ambient pressure, the thermodynamic stable configuration is the ferromagnetic configuration at temperatures from 0 K to above 1200 K. 20 However, the statistical probability of the stable ferromagnetic configuration starts to decrease around 230 K and become lower than 50% at temperatures higher than 460 K with the rest being the combination of over 500 nonstable spin-flipping configurations, resulting in a negative thermal expansion between 289 and 449 K. 21 Similar observations were made for Ce with only three configurations considered 22 and other materials. 18,19,23,24…”
Section: Mg Complexesmentioning
confidence: 99%
“…Liu et al [133,134] explained the NTE behaviour in terms of configurational entropy of metastable states, which might be viewed as the excited states of the anharmonic phonon oscillators. In NTE compounds, the mean atomic distance in the metastable state is smaller than that in the ground state configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [ 23 ] improved the Bruggeman equation based on irregular particle shape, particle content, and interface thermal resistance as follows: …”
Section: Thermal Characteristics Mechanism and Model Of Compositesmentioning
confidence: 99%
“…This is the source of vibration for thermal expansion. When the degree of separation of atoms is symmetrical to the potential energy, zero thermal expansion occurs, and NTE is the same as shown in Figure 3 [ 23 ]. In Figure 3 a, the ordinate V(r) is the potential energy of the interaction between atoms, and the abscissa r is the size of the interaction distance between the atoms.…”
Section: Thermal Characteristics Mechanism and Model Of Compositesmentioning
confidence: 99%